2005
DOI: 10.1111/j.1469-8137.2005.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable tolerance of wetland tree species to combined salinity and waterlogging is related to regulation of ion uptake and production of organic solutes

Abstract: Summary• Melaleuca cuticularis and Casuarina obesa occur in wetlands, whereas Banksia attenuata occurs in adjacent well-drained sandy soils. Salt and waterlogging tolerances in these tree species were studied, as the levels of these stresses have increased in south-western Australia.• Seedlings were exposed to 0.01, 200 or 400 m M NaCl, with or without waterlogging, in a sand culture with nutrient solution for 22 d in a glasshouse.• Melaleuca cuticularis and C. obesa survived all treatments, and generally main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 46 publications
3
51
1
Order By: Relevance
“…The lowest values of Pc (0.1 mg g -1 FW for wheat and 0.05 mg g -1 FW for bean) are observed at the lowest salinity level at 6 kPa matric suction. The decrease in Pc with aeration improvement has been observed by many researchers (Carter et al, 2006). The Pc increases with matric suctions between 6 and 10 kPa and then remains nearly constant, for both crops.…”
Section: Resultsmentioning
confidence: 88%
“…The lowest values of Pc (0.1 mg g -1 FW for wheat and 0.05 mg g -1 FW for bean) are observed at the lowest salinity level at 6 kPa matric suction. The decrease in Pc with aeration improvement has been observed by many researchers (Carter et al, 2006). The Pc increases with matric suctions between 6 and 10 kPa and then remains nearly constant, for both crops.…”
Section: Resultsmentioning
confidence: 88%
“…Water and salt stress have profound effects on plant survival (Ladiges et al 1981, Munns and Termaat 1986, Munns 2002, Carter et al 2006, Salter et al 2008) and species composition (James et al 2003, Nielsen et al 2003, Smith et al 2009). Importantly, the nature of the relationship between plant survival and species composition with increasing salinization often conforms to a sigmoidal model (Carpenter 2003, Davis et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the accumulation of proline analogues in leaves of 125 Melaleuca species, Naidu et al (2000) showed a possible relationship between salt tolerance and the kinds and number of different proline analogues plants accumulate. Furthermore, Carter et al (2005) suggested that the salt-induced accumulation of methyl proline in M. cuticularis is sufficient to provide osmotic balance in the cytoplasm, consequently contributing to salt tolerance. Under salt stress, the decrease in OP with an accumulation of organic osmoprotectants such as proline is one Refer to the footnote in Table 2 mechanism by which plant cells uptake water and thus maintain cell turgor (Neumann et al 1988).…”
Section: Effects Of the Interaction Between Al And Naclmentioning
confidence: 98%